Determining the influence of raw milk protein composition on the yield of cheese and its nutrient content - Ladyka, Volodymyr; Bolgova, Natalia; Synenko, Tetiana; Skliarenko, Yuriy; Vechorka, Viktoriia (Eastern-European journal of enterprise technologies, 2023)
Cheese production is a complex process that is influenced by many factors: protein:fat ratio, acidity, and type of rennet. An option for improving the profitability of the cheese industry is the genetic selection of dairy cows to produce milk with good rennet protein coagulation. The object of the study is the technology of cheeses made from milk from cows with different β-casein genotypes (А1А1, А1А2, А2А2). The subject of the study is the physical-chemical parameters of milk from cows with different genotypes for β-casein; yield of cheese from this milk and its quality indicators. Samples of Gouda cheese were produced according to traditional technology. The research established that the quality indicators of milk samples are typical for fresh cow's milk. The content of fat, protein, and dry matter in the milk of cows with the β-casein genotype A2A2 were slightly higher compared to A1A1 and A1A2. The study of the quality indicators of the cheese samples showed that the type of β-casein did not affect the organoleptic properties of the cheese. However, according to the content of the main chemical components, cheeses made from A1A2 milk had a higher content of dry matter and protein (61,6 % and 19,2 % on average, respectively) and a lower fat content (37.2 %). The amino acid profile of cheese from milk of cows with β-casein A1A2 and A2A2 genotypes showed a higher total content of amino acids – 14.89 mg/g and 13.84 mg/g, respectively. Calculations of cheese yield showed that cheese yield from milk of cows with β-casein genotype A1A2 was higher (mean value 13.1 %) than with A1A1 and A2A2. The obtained results are of practical importance, as it is possible to take into account how changes in the β-casein genotype in milk can affect the yield of cheese, and therefore, the profitability of production Виробництво сиру є складним процесом, на який впливає багато факторів: співвідношення білок:жир, кислотність, тип сичужного ферменту. Варіантом покращення рентабельності сироробної галузі є генетичний відбір молочних корів для отримання молока з хорошим сичужним зсіданням білку. Об’єктом дослідження є технологія сирів твердих виготовлених з молока-сировини від корів з різними генотипами за β-казеїном (А1А1, А1А2, А2А2). Предметом дослідження є фізико-хімічні показники молока від корів з різними генотипами за β-казеїном; вихід твердого сиру з цього молока та його якісні показники. Зразки твердого сиру «Гауда» виготовляли за традиційною технологією. Проведеними дослідженнями встановлено, що фізико-хімічні показники молока-сировини від корів з різними генотипами β-казеїну є типовими для свіжого коров’ячого молока. Вміст жиру, білка та сухих речовин в молоці корів з генотипом β-казеїну А2А2 були дещо вищими порівняно з А1А1 та А1А2. Комплексне дослідження показників якості зразків твердих сирів показало, що тип β-казеїну не впливав на сенсорні характеристики сиру. Проте за вмістом основних хімічних компонентів сири, виготовлені з молока А1А2, мали вищий вміст сухої речовини та білка (в середньому 61,6 % та 19,2 % відповідно) та нижчий вміст жиру (37,2 %). Амінокислотний профіль сиру з молока корів з генотипом за β-казеїном А1А2 і А2А2 показав вищий загальний вміст амінокислот – 14,89 мг/г та 13,84 мг/г відповідно. Розрахунки виходу сиру показали, що вихід сиру з молока корів з генотипом β-казеїну А1А2 був вищим (середнє значення 13,1 %), ніж з А1А1 та А2А2. Отримані результати мають практичне значення, оскільки можна врахувати, як зміни генотипу β-казеїну в молоці-сировині можуть впливати на вихід сиру, а отже, і на прибутковість виробництва